Exploring the Impact of Marital Satisfaction on Subjective Well-Being among Married Individuals of Pakistan - Sahar Naveed; Dr. Aafia Rasool (Research Journal of Psychology, 2025)
This study looks into the increasing challenge of marital satisfaction and its effects on people’s well-being in Pakistan. The main goal is to see how satisfaction within marriage can influence a person’s well-being, especially subjective well-being. Using a cross-sectional approach, this research gathers data from married individuals across cities of Pakistan through validated questionnaires to ensure a wide range of perspectives. The total sample size was 329. The males were 124 and 205 were females, the Mean age was 33.45 with a standard deviation of 9.10. The instruments used for collecting responses were the Couple Satisfaction Index and SPANE (Scale of Positive and Negative Experience) for Subjective Well-Being Scale. By applying correlation, regression, and independent t-test, it identifies significant links between marital satisfaction, subjective well-being, and demographics. The correlation finding shows that a significant relationship exist between marital satisfaction and the dimensions of subjective well-being as a positive correlation was found between marital satisfaction and Positive Experience, but a significant negative correlation was found between marital satisfaction and Negative Experience. Regression analysis shows that marital satisfaction significantly predicts the dimensions of subjective well-being. The t-test analysis showed that there was no gender difference noted in marital satisfaction and positive experience subscale of SPANE but a significant difference in the negative experience subscale was found between the SPANE measures among both genders. These results emphasize the value of nurturing healthy marriages, which can positively impact individuals and communities. With these insights, the study aims to guide future counseling approaches and policies to support and improve marital relationships and overall well-being in Pakistan.